Incidence of Fusarium species and levels of fumonisin B1 in corn in the Samsun province of Turkey - Altıparmak, Gülay; Tunali, Berna (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2009)
The contamination of corn with fumonisin produced by Fusarium species represents an important risk for humans and animals. The incidence of Fusarium spp. and contamination by fumonisin B1 (FB1) were studied in field samples from 70 fields of corn during the 2005 and 2006 preharvest seasons in the province of Samsun, Turkey. Fusarium was the predominant genus isolated from the field samples, with F. verticillioides, F. proliferatum and F. subglutinans being the most commonly isolated species. The occurrence of Fusarium spp. varied each year, from 97.14% to 78.57% in 2005 and 2006, respectively. The widespread occurrence of FB1 was also observed across the Samsun province. All corn samples infected with F. verticillioides, F. proliferatum and F. subglutinans tested positive for FB1, but none were infected with FB2. Levels of FB1 ranged from 0.28 to 8.48 mg kg-1 in 2005 and from 0.11 to 2.77 mg kg-1 in 2006. The concentration of FB1 was lower than 2 mg kg-1 in 63.6% of the samples, 28.8% contained from 2 mg kg-1 to 5 mg kg-1, while 7.6% contained more than 5 mg kg-1. Our study shows that corn contamination with both Fusarium and FB1 was present throughout the Samsun province, but it was strongly dependent on environmental and seasonal conditions. However, there was no Fusarium contamination in certain native white-type and popcorn-type cultivars in 2005 and 2006.